Viewing mistresses Filipina audiences constructing meanings of gender & sexuality in media and everyday life - Martinez-Erbite, Ma. Kristina
Mistress narratives in films and television programs are entangled with discourses on social, cultural, and political climate of the Philippines in different historical periods. Strong forces in the Philippine society such as the legal laws and national policies supporting family and marriage, dogmatic Church teachings on morality, local culture and values, and the changing gender and sexuality norms set social parameters and influence the dominant views of people about mistresses. This study argues that, social change reconfigures the images of mistresses in film and real life. Simultaneously, women as audience construct daily meanings on what they view on films and television programs. To map the emerging representations of mistresses, this study utilize Foucauldian notions of discourse and power, and Abu Lughod's notions of everyday resistance to look at the status and images of mistresses in society, politics and movies from 1970s up to 2017. Through feminist media ethnography, this study describes how the urban poor women actively make meanings in what they perceive in media and how they accommodate, contextualize and resist media influences in their everyday gendered lives as they confront multiple realities in the urban poor community. My study argues that, dominant mistress views must be challenged, and the emerging representation of mistresses must be examined based on their symbolic, functional and cultural values.